Correcting accounting results of tensions using fem by Hss method - Bannikov, D. O.; Huslista, A. E. (Science and Transport Progress, 2011)
The usage of the Hot Spot Stress (HSS) method by means of linear surface extrapolation (LSE) approach was analyzed for the correction of results of the Finite-Element Method (FEM) in case of singularity of stresses. The given examples of structures and testing examples were computed on the base of design-and-computation software SCAD for Windows (version 11.3).